Should the Fed regularly evaluate its monetary policy framework? - Jeffrey C. Fuhrer; Giovanni P. Olivei; Eric S. Rosengren; Geoffrey M. B. Tootell (Federal Reserve Bank of Boston, 2018)
Would a more open and regular evaluation of the monetary policy framework improve policy in the United States? Even when considering a relatively short timeframe that spans the 1960s to the present, it is possible to point to many significant changes to the framework. Some of the changes were precipitated by acute economic conditions, while others were considered and implemented only gradually as a response to long-standing problems with the framework. But the process for evaluating and changing frameworks to date has not always been transparent, and changes have not always been timely. Could a more formal, and open, review improve how well we adhere to our current framework? Could transitions to a new framework be made more effectively? We conclude that such a review might indeed be beneficial, and outline one possible review process.
Keywords: E52; E58; E61; 330; monetary policy framework; the evolution of monetary policy; FOMC; policy rules